2011
DOI: 10.1177/147323001103900549
|View full text |Cite
|
Sign up to set email alerts
|

Dural Metastasis of Atypical Extraventricular Neurocytoma with the Codeletion of Chromosomes 1p/19q

Abstract: Extraventricular neurocytoma (EVN) is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Stapleton et al recently reported a rare case in the pediatric population of a diffuse CN with craniospinal dissemination that was identified at the time of the initial diagnosis by the immunohistochemical results of an elevated Ki-67 proliferation index (53). To date, there have been five reported cases of EVN with craniospinal dissemination (8,30,49,5456), including four males (7, 24, 48 and 75 years old) and one female (71 years old). Two of the patients showed drop dural metastasis and one tumor was initially located in the sellar region and was associated with multiple remote disseminations in the spinal cord and drop metastasis in the frontal cranial base in the route of the initial surgery (54).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stapleton et al recently reported a rare case in the pediatric population of a diffuse CN with craniospinal dissemination that was identified at the time of the initial diagnosis by the immunohistochemical results of an elevated Ki-67 proliferation index (53). To date, there have been five reported cases of EVN with craniospinal dissemination (8,30,49,5456), including four males (7, 24, 48 and 75 years old) and one female (71 years old). Two of the patients showed drop dural metastasis and one tumor was initially located in the sellar region and was associated with multiple remote disseminations in the spinal cord and drop metastasis in the frontal cranial base in the route of the initial surgery (54).…”
Section: Discussionmentioning
confidence: 99%
“…Two of the patients showed drop dural metastasis and one tumor was initially located in the sellar region and was associated with multiple remote disseminations in the spinal cord and drop metastasis in the frontal cranial base in the route of the initial surgery (54). The other tumor was initially located in the left occipital-parietal lobe and was associated with drop metastasis along the frontotemporal dura with an intratumoral hemorrhage outside the field of the initial surgery (56). The initial tumor of the patient in the present case report was located in the right frontal lobe.…”
Section: Discussionmentioning
confidence: 99%